Perancangan Antarmuka Pengguna Aplikasi Leson menggunakan Metode Human-Centered Design (HCD) - Adam Surya Wibawa; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
UB Learning Technology develops an application called LESON (Lesson Study Observation Note) to support supervision evaluation activities via mobile devices. Currently this application is still under development. So, the developer decided to make changes, especially in the appearance of the LESON application, which is currently considered less attractive. To help design the LESON application the Human-Centered Design (HCD) method is used to help develop interactive User Interface designs and the Heuristic Evaluation method, where the role of UI / UX experts as evaluators is to help UX Designers in producing good and correct solution designs. There are four stages carried out, namely the stage of analyzing the context of use and user needs, starting with conducting interviews with stakeholders and users in supervision activities. The result of the information obtained is that the application will have two users, namely the model teacher and the supervisor. Then the solution design stage is carried out based on the results of the user needs analysis seen from the evaluations that have previously been carried out. Then the evaluation stage is carried out with the results of usability testing using the SUS questionnaire by users of the Information Systems Study Program students. Then an evaluation was carried out using the heuristic evaluation method by three UI / UX expert evaluators which showed that a total of twenty-five problems were found in the solution design design. Based on the results of the average severity rating on the whole problem, it was found that sixteen problems had a high enough score, namely above two. The repair stage was carried out on these problems, leaving zero problems.